Effect of Duration and Number of Subjects on Students' Performance in Junior Clerkship - Sahira Aaraj; Ayisha Kausar; Fareeha Farooqui (J. Islamic Int. Med. Coll., 2024)
Objective: In the current study we evaluated the impact of the number of examination subjects and the length of teaching duration on student performance in the fourth professional examination. Study Design: Comparative cross-sectional study. Place and duration of Study: Shifa College of Medicine, Islamabad from 1 Jan 2021 to 30 June 2022. Materials and Methods: The study enrolled 220 students from the batches of year 2021 and 2022. We analysed the effect of duration of the clinical teaching (2 years vs. 3 years) and the effect of number of examining subjects in professional examination (3 subjects vs. 4 subjects) on the students' final scores. The data was analysed by SPSS version 23.0. The mean scores and standard deviation for theory and objectively structured clinical exam (OSCE) were compared using independent sample t-test. The results were also compared for the number of failing students and high scores (> 80 %) between two study cohorts. The p value of ≤ 0.05 was considered statistically significant. Results: No statistically significant difference was found in the scores of ophthalmology theory /OSCE, gynaecology & obstetrics (OB/GYN), ENT theory and pediatric OSCE. The mean scores were significantly better in OB/GYN OSCE (p value < 0.015) and ENT OSCE (p value <0.001) after 2 years of teaching/ four subjects in professional examination respectively. Pediatrics theory results showed a decline after two years of teaching as compared to three years of teaching (p value < 0.001). Conclusion: The number of years of clinical teaching and the total number of subjects in professional examination have no impact on students' academic performance in fourth professional examination.